PRAKTIK PENGELOLAAN ZAKAT PROFESI DI BADAN AMIL ZAKAT NASIONAL KABUPATEN BATU BARA - Sirait, Nilna Mayang Kencana; Fikri, Hasanul (Jurnal Ilmiah Al-Hadi, 2019)
Zakat is a worship that contains of two dimensions are dimension of hablum minallah or vertical domension and dimension of hablumminannas or horizontal dimension. If we do the zakat worship well, our faith quality will be increas, cleaning our heart, developing and blessing the treasure we have. When the treasure can be managed and mandate well, zakat is able to increas the people well being, ethos and work ethics, and as economic tightening institution. The golden age of Islam, zakat has opened hardly for increasing the people well-being. Zakat is managed very well and distribution aqually until to the right place.